Care and feeding of a staff for filmless radiology...Proccedings of the 16th Symposium for Computer Applications in Radiology. 'PACS: Performance Improvement in Radiology.' Houston TX, May 6-9, 1999 - Mensch B; Honea R; Orand M (Journal of Digital Imaging)
Texas Children's Hospital, a definitive care pediatric hospital located in the Texas Medical Center, has been constructing a large-scale picture archival and communications system (PACS) including ultrasound (US), computed tomography (CT), magnetic resonance (MR), and computed radiography (CR). Developing staffing adequate to meet the demands of filmless radiology operations has been a continuous challenge. Overall guidance for the PACS effort is provided by a hospital-level PACS Committee, a department-level PACS Steering Committee, and an Operations Committee. Operational Subcommittees have been formed to address service-specific implementation, such as the Emergency Center Operations Subcommittee. These committees include membership by those affected by the change, as well as those effecting the change. Initially, personnel resources for PACS were provided through additional duties of existing imaging service personnel. As the PACS effort became more complex, full-time positions were created, including a PACS Coordinator, a PACS Analyst, and a Digital Imaging Assistant. Each position requires a job description, qualifications, and personnel development plans that are difficult to anticipate in an evolving PACS implementation. These positions have been augmented by temporary full-time assignments, position reclassifications, and cross-training of other imaging personnel. Imaging personnel are assisted by other hospital personnel from Biomedical Engineering and Information Services. Ultimately, the PACS staff grows to include all those who must operate the PACS equipment in the normal course of their duties. The effectiveness of the PACS staff is limited by their level of their expertise. This report discusses our methods to obtain training from outside our institution and to develop, conduct, and document standardized in-house training. We describe some of the products of this work, including policies and procedures, clinical competency criteria, PACS inservice topics, and an informal PACS newsletter. As the PACS system software and hardware changes, and as our implementation grows, these products must to be revised and training must be repeated. Copyright (c) 1999 by W.B. Saunders Company